A Strategic Vision for Combating Cyberterrorism - Mathkar Alsubaie (Journal of Information Security and Cybercrimes Research, 2021)
Cyberterrorism has become a well-known cybersecurity subject in today's digital world. The spread of cybercrimes calls for disseminating ethical values and peace between countries and individuals. Because of this phenomenon's danger to society, this study sought to lay down directives for security strategies to confront cyberterrorism. Hence, the study's main research problem revolves around highlighting the role of security authorities in addressing cyberterrorism according to the specialists in information technology (IT) centers in Saudi universities in Riyadh. Hence, a descriptive analysis method was adopted as a research methodology. We distributed questionnaires as a study tool to 150 specialists in IT centers in Saudi universities in Riyadh. The study yielded different views regarding the types and ways of cyberterrorism committed through the internet. Results showed the respondents' opinions regarding the essential types of cyberterrorism. Moreover, they emphasize the need to raise awareness in dealing with cyberterrorism by enforcing cybersecurity with the most prominent means and procedures that the authorities are responsible for. The most critical recommendations are: (1) the need to provide the employees with the technical skills to know how to deal with any potential security breach, (2) the need to provide specialized training courses in protection methods for workers, and (3) the need to develop the means of security and legal protection through developing e-government security agreements.